Local Product Brand Image: A Case Study of Small and Medium Enterprises in Muar, Johor. - Hasmah Zanuddin; Norrosellah Mukhtar (International Journal of Supply Chain Management, 2019)
Malaysia, which has a variety of races and cultures, is booming with commercial activities. Currently, small and medium enterprises in Malaysia have received increasing attention from the public and government.Today, brand plays important roles which is to improve consumers lives and enhance the financial values of firms. It can also differentiate companies products with those of competitors.Strong brands dont just happen. They are usually the results of a long-term strategy that guides how a company does business and is tightly bound to its understanding of customer needs.The focus of this research is an examination of brand and branding of local products produced by small and medium enterprises of local people at Bandar Muar, Johor. Branding theory signifies three important frameworks for this study, namely symbol, communication and behavior. Overall,branding benefits in terms of customer recognition. The brand image plays an important role when a customer decides to buy one product over another. Usually, well-established brands have good reputations and are immediately recognizable to consumers. Almost 86 percent customers who have been interviewed prefer good and attractive packaging, which is reflected in symbol framework. Around 82 percent customers demand that communication element uses all mediums of communication for wider reach. The most preferred product branding behavior by local customers and local product is equivalent competitive standing for local and foreign products. Basically, well-known brands are likely to be purchased rather than those that are unknown. People often trust what they know and distrust, or, at the very least, feel suspicious with unknown brands.